1981
DOI: 10.1128/jcm.13.6.1011-1016.1981
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of diarrhea in calves infected with rotavirus and enterotoxigenic Escherichia coli

Abstract: The susceptibility of gnotobiotic, colostrum-derived, or suckling calves to four bovine rotavirus isolates was found to be age dependent. Calves older than 7 days remained clinically normal, although they excreted virus in their feces and subsequently developed antibody against the virus, Enterotoxigenic Escherichia coli, fed to gnotobiotic, colostrum-deprived, or suckling calves ranging in age from a few hours to 26 days old, only caused diarrhea in animals younger than 24 h old. In contrast, diarrhea was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 14 publications
4
23
0
Order By: Relevance
“…However, in conventional calves in this ex-periment ETEC ,colonisation occurred in the presence of rotavirus infection while ETEC were eliminated in the absence of rotavirus infection. This supports the observations made by Tzipori et al (1981). Thus in this study the interaction of rotavirus and ETEC in the intestine may be classed as synergistic rather than additive.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in conventional calves in this ex-periment ETEC ,colonisation occurred in the presence of rotavirus infection while ETEC were eliminated in the absence of rotavirus infection. This supports the observations made by Tzipori et al (1981). Thus in this study the interaction of rotavirus and ETEC in the intestine may be classed as synergistic rather than additive.…”
Section: Discussionsupporting
confidence: 92%
“…However, experiments with gnotobiotic animals exaggerate the ability of microorganisms to colonise the intestine, and the interaction of two organisms can more realistically be studied against the background interaction with a normal gut flora. Preliminary experiments by Tzipori et al {1981) showed that rotavirus and ETEC inoculated together into conventional calves produced a more severe diarrhoea than that caused by either agent alone. The present study was therefore undertaken to investigate the interaction of rotavirus and ETEC in the production of diarrhoea in conventionally-reared calves aged 6 days.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of multiple infections with enteropathogens has been investigated experimentally by a number of investigators. 16,25,51,55,60,66,81,82,84 Direct comparisons between these studies is difficult because of differences in the ages of animals used, virus and bacterial isolates, dosages, and feeding regimens. In general, these studies have shown that simultaneous inoculations of calf rotavirus and enterotoxigenic E. coli cause a more severe diarrhea than either agent causes alone, but the effect is additive and not synergistic.…”
mentioning
confidence: 99%
“…The bovine rotavirus C6 used in this experiment was isolated from a field outbreak of calf diarrhoea as described previously (Tzipori et al, 1981a). Fifteen ml aliquots of faecal filtrates (20%, v/v) which contained between 10 ~ and l0 s particles per ml, as assessed by electron microscopy (EM), were used as standard inoculum for each calf.…”
Section: Virologymentioning
confidence: 99%
“…In a previous communication (Tzipori et al, 1981a) it was established that co-infection of older calves with ETEC and rotavirus precipitates diarrhoea 36 in circumstances where each agent alone did not. In this study we have examined the nature of this dual infection and its effect on the intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%